An investigation into the mechanistic behaviour of RAFT-mediated miniemulsion polymerizations. - Hermant, Marie-Claire (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2005.